Measurement of effective dose to patient during interventional cardiac procedure - Siraz, MMM; Begum, Aleya; Khan, RK; Hoque, A; Begum, A (Journal of the Asiatic Society of Bangladesh, Science, 2014)
Interventional cardiac procedures result in substantial patient radiation dose due to prolonged fluoroscopy time and radiographic exposure. Patient dose measurement is performed in two catheterization laboratories in Square Hospital Ltd, Dhaka. A total of 50 patients of Square Hospital is included in this study. TLDs are used for the measurement of the dose received by patients during interventional cardiology at Square Hospital, Dhaka. Patients, who underwent CAG, PTCA, and (CAG with PTCA) have average effective dose 3.30 mSv with a range from 0.96 to 9.12 mSv, 24.14 mSv with a range from 7.56 mSv to 56.81 mSv and 25.56 mSv with a range from 1.21 mSv to 95 mSv respectively. Our results correspond well with those obtained by authors in other countries of the world. This study would be useful to establish a database of the patients dose for CAG and PTCA. This may lead cardiologists and scientists to adopt necessary safety measures for reducing exposure to patients and occupational workers. J. Asiat. Soc. Bangladesh, Sci. 40(1): 1-7, June 2014